Does South African Affirmative Action Policy Reduce Poverty? A CGE Analysis. Issue 3 (September 2016) - Maisonnave, Hélène; Decaluwe, Bernard; Chitiga, Margaret
Abstract : This article presents a computable general equilibrium model (CGEM) able to measure the impacts of the affirmative action policy set up in South Africa. In order to decrease inequalities inherited from the former regime, the government encourages firms to employ historically disadvantaged persons. Through this study, we evaluate the impact of this policy on employment, poverty, and inequality using a CGE top‐down approach. The article analyzes one scenario that deals with the impact of affirmative action on skilled jobs. Results show a deep decrease in unemployment and poverty for each population group.